The 1926 novel, “One, no one, one hundred thousand”, metaphorizes the potential danger when the immune system is exposed to a repetitive antigen stimulation - Ferrazzo, Francesca; Leto, Sara; Malara, Natalia (Frontiers in Immunology, 2023)
In the worldwide scenario of infection prevention and control, the vaccine strategies are destined to increase rapidly. The availability of numerous vaccination options allows you to plan individually on how to boost your immune system. The immune system is a highly plastic cognitive dynamic network and performs its function by recognition of the uniqueness of the organism defined as self. The identification and attack of non-self antigens contribute to improving the strategies of self/non-self discrimination. However, repetitive antigen stimulation of the immune system may lead to several outcomes reassumed in three principal risks: (i) loss of the unique self codification (one), (ii) loss of own identifying (no one), and (iii) the increase of idiotype/anti-idiotype entities (one hundred thousand). Controlled production of idiotype/anti-idiotype antibodies protects against autoimmune diseases and immunodeficiency. The title of the famous novel by Nobel Prize for Literature winner Luigi Pirandello, “One, no one, one hundred thousand”, recaps the three risks and the protagonist’s journey exploring the complexities of personal identity, and warns to preserve the uniqueness of the organism. Taking inspiration from this metaphor, the authors propose to monitor antibody idiotype response for personalizing vaccine plans with the aim of preserving the uniqueness of the immune system and assuring safe protection.